2011
DOI: 10.1253/circj.cj-10-0956
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Prognosis of Adaptive Servo-Ventilation Therapy in Patients With Heart Failure

Abstract: Background: This study tested the hypothesis that adaptive servo-ventilation (ASV) therapy improves the prognosis of heart failure (HF) patients, regardless of the severity of sleep-disordered breathing (SDB). Methods and Results:88 consecutive patients were divided into 4 groups based on ASV therapy and SDB severity. The incidence of HF, brain natriuretic peptide (BNP) levels, and left ventricular ejection fraction (LVEF) were followed for 12 months. Fewer HF events, together with an increase in LVEF and a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Furthermore, based on data showing the acute beneficial effects of short-term ASV application on sympathetic nervous system activity [33,34] and hemodynamics [35] , ASV may be a more promising therapeutic option for chronic HF patients without SDB. In fact, Koyama et al [122] reported that ASV was associated with better clinical outcomes, regardless of the presence or absence of moderate CSA (i.e., AHI < 20 or ≥ 20). The possible benefits of ASV on cardiac function are being assessed in an ongoing randomized clinical trial in which HF patients with and without SDB are being randomized to either ASV treatment or medical therapy to assess the changes in LV ejection fraction at 6 mo [123] .…”
Section: Chronic Hf Patients Without Sdbmentioning
confidence: 99%
“…Furthermore, based on data showing the acute beneficial effects of short-term ASV application on sympathetic nervous system activity [33,34] and hemodynamics [35] , ASV may be a more promising therapeutic option for chronic HF patients without SDB. In fact, Koyama et al [122] reported that ASV was associated with better clinical outcomes, regardless of the presence or absence of moderate CSA (i.e., AHI < 20 or ≥ 20). The possible benefits of ASV on cardiac function are being assessed in an ongoing randomized clinical trial in which HF patients with and without SDB are being randomized to either ASV treatment or medical therapy to assess the changes in LV ejection fraction at 6 mo [123] .…”
Section: Chronic Hf Patients Without Sdbmentioning
confidence: 99%
“…9 Koyama et al have also reported that ASV therapy for patients with HF effectively improved the short-term prognosis (again, assessed by LVEF and BNP), irrespective of the SDB severity. 21 Moreover, previous reports have revealed that ASV therapy improved both BNP and LVEF. 2,3,21,22 The results of the present study are therefore consistent with previous findings.…”
Section: Findings and Data Interpretationmentioning
confidence: 97%
“…21 Moreover, previous reports have revealed that ASV therapy improved both BNP and LVEF. 2,3,21,22 The results of the present study are therefore consistent with previous findings.…”
Section: Findings and Data Interpretationmentioning
confidence: 97%
See 1 more Smart Citation
“…SDB is usually treated with noninvasive positive pressure ventilation (NPPV), which includes continuous positive airways pressure (CPAP), bi-level positive airway pressure (Bi-PAP) and adaptive servo-ventilation (ASV). NPPV can improve respiratory disturbances to different degree, and thereafter reduce venous return, cardiac preload and pulmonary congestion [35]. NPPV has been recommended and widely used in the respiratory management of patients with acute heart failure (AHF) [6, 7].…”
Section: Introductionmentioning
confidence: 99%